If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(3x + 8a) = b + -18x Reorder the terms: a(8a + 3x) = b + -18x (8a * a + 3x * a) = b + -18x Reorder the terms: (3ax + 8a2) = b + -18x (3ax + 8a2) = b + -18x Solving 3ax + 8a2 = b + -18x Solving for variable 'a'. Reorder the terms: 3ax + 8a2 + -1b + 18x = b + -1b + -18x + 18x Combine like terms: b + -1b = 0 3ax + 8a2 + -1b + 18x = 0 + -18x + 18x 3ax + 8a2 + -1b + 18x = -18x + 18x Combine like terms: -18x + 18x = 0 3ax + 8a2 + -1b + 18x = 0 The solution to this equation could not be determined.
| -(1+4n)=-2n-13 | | m(m+8)=0 | | 6-24x^2-8x^4= | | -11=7n | | -4u=56 | | 3r(r+4)=0 | | 11n=-55 | | -9w=-81 | | (x-3)(7x+5)=0 | | -7(n+8)=-91 | | r-11=-27 | | 3x^2+14x-24=0 | | b(b+7)=0 | | 10b=-10 | | -17+x=-19 | | 7x(3x+8)=0 | | 4x+3=3-(x-23) | | x=11y | | (x-4)(x-8)=0 | | 36=7x-12-10x | | 4(2x-1)=3(6+3x) | | 7(-6x+5)=-259 | | (p+8)(p-8)=0 | | 7-(6x+5)=-259 | | 8(5n+1)(3n+4)=0 | | 6(x+3)(x-7)=0 | | 7(x+6)(3x+1)=0 | | -(4y+2)-(-3y-5)=2 | | -3(4+4x)=-84 | | -5(x+3)=25 | | 5x-3=3x+10 | | m^2-2m-63=0 |